فاعلية إستراتيجية تدريس الأقران في تنمية مهارات القراءة لدى طلاب الصف الثالث المتوسط بمدينة جدة - الزهراني، نايف بن عقال بن شريم (جامعة كفر الشيخ - كلية التربية, 2020)
هدف البحث إلى الكشف على فاعلية استخدم استراتيجية تدريس الأقران في تنمية مهارات القراءة الجهرية لدى طلاب الصف الثالث المتوسط، ولتحقيق هذا الهدف استخدم الباحث المنهج شبه التجريبي القائم على التصميم التجريبي للمجموعتين التجريبية والضابطة وقد تكونت عينة البحث من ستين طالبا مقسمين إلى مجموعتين، كل مجموعة تضم ثلاثين طالبا من طلاب الصف الثالث المتوسط، وشملت أدوات البحث: استبانة تضمنت قائمة بمهارات القراءة الجهرية المناسبة لطلاب الصف الثالث المتوسط، واختبارا لقياس مهارات القراءة الجهرية، وقد أظهرت النتائج وجود فروق ذات دلالة إحصائية عند مستوى (α≤0.05) بين متوسطي درجات طلاب المجموعة التجريبية وطلاب المجموعة الضابطة في التطبيق البعدي لاختبار مهارات القراءة الجهرية، لصالح الطلاب في المجموعة التجريبية، ووجود فروق ذات دلالة إحصائية عند مستوى (α≤0.05) بين متوسطي درجات طلاب المجموعة التجريبية في التطبيقين (قبلي- بعدي) لاختبار مهارات القراءة الجهرية لصالح التطبيق البعدي، وقد أوصت الدراسة بالاهتمام بتنمية مهارات القراءة الجهرية من خلال تطوير طرائق التدريس الحالية، والبعد عن الطرائق التقليدية مع العمل على زيادة مشاركة الطلاب بفعالية ونشاط في عملية التعلم.
The aim of the research is to discover the effectiveness of using the peer-teaching strategy in developing the skills of reading aloud among middle-grade third-grade students, and to achieve this goal, the researcher used the quasi-experimental approach, based on the experimental design of the experimental and control groups, and the research sample consisted of sixty Students are divided into two groups, each group includes thirty students, from the third intermediate grade, and the research tools included: a questionnaire that included a list of reading skills suitable for students of the third intermediate grade, and a test to measure reading skills aloud, and the results showed that there are statistically significant differences at the level of (0,05≥a) between the mean scores of the experimental group students and the control group students, in the post application of the test of reading aloud skills, for the benefit of students in the experimental group, and the presence of statistically significant differences at the level of (0.05≥a) between the mean scores of students The experimental group in the two applications (before - after) to test the skills of reading aloud, in favor of the post application, and the study recommended attention to developing skills of reading aloud, through the development of current teaching methods, and the distance from the methods Traditional, with the active and active participation of students in the learning process.
Keywords: الإستراتيجيات التعليمية -- إستراتيجية تدريس الأقران -- القراءة -- الصف الثالث المتوسط -- جدة